Exploration of the Mechanisms of Acorus tatarinowii in the Treatment of Major Depressive Disorder Based on Network Pharmacology and Molecular Docking Techniques - Li Han; Siwen Wei; Rong Wang; Yiran Liu; Yi Zhong; Huaiqing Luo (Current Issues in Molecular Biology)
Objective: To elucidate the molecular targets and mechanisms by which Acorus tatarinowii exerts therapeutic effects in major depressive disorder (MDD) using network pharmacology and molecular docking approaches. Methods: Bioactive compounds of Acorus tatarinowii were identified from comprehensive pharmacological databases. MDD-related targets were sourced from extensive genomic repositories. Overlapping targets were determined and subjected to network topology and protein–protein interaction (PPI) analyses to identify core targets. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were performed to reveal pertinent biological processes and signaling pathways. Molecular docking simulations validated the interactions between key bioactive compounds and core targets. Results: A total of 57 bioactive compounds were identified in Acorus tatarinowii, including apigenin, heterotropan, and isoelemicin. Integrative analysis revealed 700 compound-related targets and 2590 MDD-associated targets, with 150 intersecting targets. Network analyses pinpointed five core targets: TP53, STAT3, AKT1, PIK3CA, and PIK3R1. GO enrichment identified 858 significant biological processes, while KEGG pathway analysis highlighted 155 enriched pathways, notably the PI3K-Akt, cAMP, and MAPK signaling pathways. Molecular docking studies demonstrated strong binding affinities between key compounds and their respective targets. Conclusions: This study delineates the multifaceted polypharmacological mechanisms through which Acorus tatarinowii may confer protective effects against major depressive disorder, underscoring its potential as a promising therapeutic agent.